History of endodontics: from science to practice (Эндодонтия Today)
From the moment of opening of antibiotics, improvement of stomatology materials and tools, and also the endodontics of technologies allowed to increase significantly an indicator of success of endodontics therapy for the last hundred years. Results of treatment of special cases which were considered hopeless earlier, such as treatment the periapex of complications, reached high levels of clinical success now. Thanks to efforts of scientists and clinical physicians viability of tooth without pulp can be maintained the long period.